2010
DOI: 10.1016/j.neuropharm.2009.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of hindbrain vasotocin in goldfish are seasonally variable but not sexually dimorphic

Abstract: We have previously demonstrated that centrally administered vasotocin (VT) inhibits social approach toward same-sex conspecifics in male and female goldfish, and that this behavioral effect is dependent upon VT projections to the hindbrain. We now show that there are no sex differences in sensitivity to the behavioral effects of VT, though differences do exist in responsiveness across seasons in both sexes. A central dose of 1 µg, but not 200 ng, inhibited social approach in goldfish in non-reproductive condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…In our experiments, IT had no significant effects on grouping behaviour, suggesting at the very least that this homologue of oxytocin does not function as a broadly prosocial neuropeptide in zebrafish and does not mediate increased group cohesion. Furthermore, while AVT and IT have sometimes been described as 'male' and 'female' nonapeptides, the responses of the female subjects to AVT but not to IT, as well as the data of others (Walton et al, 2010) do not support this view.…”
Section: Isotocinmentioning
confidence: 74%
See 2 more Smart Citations
“…In our experiments, IT had no significant effects on grouping behaviour, suggesting at the very least that this homologue of oxytocin does not function as a broadly prosocial neuropeptide in zebrafish and does not mediate increased group cohesion. Furthermore, while AVT and IT have sometimes been described as 'male' and 'female' nonapeptides, the responses of the female subjects to AVT but not to IT, as well as the data of others (Walton et al, 2010) do not support this view.…”
Section: Isotocinmentioning
confidence: 74%
“…In goldfish ( Carassius auratus), time in proximity to conspecifics ('social approach') is modulated by nonapeptide administration: IT reduces it while AVT increases it (Thompson & Walton, 2004). These effects are seen in both sexes, however they appear to be dependent on baseline levels of social approach (Thompson & Walton, 2004) and on reproductive state in this seasonally-breeding species (Walton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We specifically examined the hindbrain tissue in this study since work by Thompson and Walton [12] suggested that VT's effect on social approach behaviours in male goldfish (Carassius auratus) might be mediated via VT action on autonomic regulatory processes in the hindbrain. Walton and coworkers [94] subsequently found evidence that gene transcript abundance for the v1a2 receptor might increase in the goldfish hindbrain during that species' reproductive season. While our results did not identify any correlative associations between hindbrain nonapeptide receptor expression and individual variation in behaviour, we did observe elevated hindbrain v1a1 and v2a mRNA levels in small, female pupfish, and future studies should continue to examine how patterns of VT receptor expression in the hindbrain may relate to social experience.…”
Section: Accepted Articlementioning
confidence: 99%
“…In the goldfish (Carassius auratus), higher levels of endogenous AVT induce social withdrawal, through neural AVT-ir projections to the hindbrain [Thompson and Walton, 2009]. Although it is not yet clear which teleost preoptic neurons project to the hindbrain, the gPOA neurons are good candidates [but see discussion in Thompson and Walton, 2009;Walton et al, 2010]. In fact, the density of AVT-ir fibres in the vagal motor nucleus (VMN; a hindbrain area with proposed participation in approach/withdrawal behaviour) is positively correlated with the number of gPOA in the Hawaiian sergeant damselfish Abudefduf abdominalis [Maruska, 2009].…”
Section: The Gpoa Cell Group and Cleaning Behaviourmentioning
confidence: 99%